2015
DOI: 10.4081/jlimnol.2015.1213
|View full text |Cite
|
Sign up to set email alerts
|

Water quality in Lake Xochimilco, Mexico: zooplankton indicators and Vibrio cholerae

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 13 publications
2
21
0
3
Order By: Relevance
“…In this study, we observed 30 species of rotifers in this lake (but 65 species in the river). The species diversity was lower than that of rotifers in the river; this trend has been reported for other lentic systems too (Nandini et al, ; Ramírez‐García et al, ). This lake also had higher densities of cyanobacteria, particularly Microcystis and Lyngbya , whereas the river had higher densities of diatoms.…”
Section: Discussionsupporting
confidence: 66%
“…In this study, we observed 30 species of rotifers in this lake (but 65 species in the river). The species diversity was lower than that of rotifers in the river; this trend has been reported for other lentic systems too (Nandini et al, ; Ramírez‐García et al, ). This lake also had higher densities of cyanobacteria, particularly Microcystis and Lyngbya , whereas the river had higher densities of diatoms.…”
Section: Discussionsupporting
confidence: 66%
“…Thus, the waterbody is oligosaprobic to β-mesosaprobic. This is similar to Lake Xochimilco with a saprobic index ranging from1.5 to 2.0 (Nandini et al, 2016). The total rotifer density was however much lower: the mean annual density was 180 ind L -1 and when data of all the five stations were combined, 11 months had mean density of < 500 ind L -1 (oligotrophic condition) while only one month (November) had close to 1000 ind L -1 (mesotrophic).…”
Section: Discussionmentioning
confidence: 54%
“…However, phosphate levels were high (annual mean 0.64 mg L -1 ). In Lake Xochimilco, Nandini et al (2016) reported nitrate levels of <1 mg L -1 , while phosphates are an order of magnitude higher (2.5-7.8mg L -1 ). On the other hand, Chl a levels in this work varied considerably (2 to 930 µg L -1 ), the mean annual concentration was 110 mg L -1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations